Relationship between Thyroid Hormones and TSH, FSH, LH, LH/FSH Ratio, Prolactin and Testosterone Hormones in Infertile Patient Women with Hyperthyroidism in Reproductive Age - Dalal Abdul Hussain Kadium (Journal of Global Pharma Technology, 2018)
Our   work  involved  studies  for  levels of thyroid  hormones (Triiodothyonine T3,Thyroxin T4) and thyroid stimulating hormone   (TSH),follicular stimulating hormone(FSH), luitienzing hormone(LH), prolactin(PRL) and testosterone hormone LH/FSH ratio  in infertile patients women with hyperthyroidism and sanitary fertile women and to find the relationship between thyroid  hormones (T3 ,T4) and TSH, FSH, LH, PRL and testosterone hormones and LH/FSH ratio, and correlation of TSH with T3,T4, FSH, LH, PRL and testosterone hormones and LH/FSH ratio in sterile women with hyperthyroidism in reproductive age. (60) sterile women with hyperthyroidism with age (19-41) years old and body weight (65. 60 ±  0.20 kg ) who recalculated Endocrine unity of Teaching Al-Sadr hospital in Al-Najaf Al-Ashraf Governorate from  1/ 9 / 2015 to 1 / 10 / 2016  , patients women group was compared with (30) fertile non- patients women with age(19-41) years old and body weight (72.35 ±  0.42 kg) as control group. The results pointed to a significant increasing(P<0.05)in levels of T3,T4, LH, PRL , testosterone  and LH /FSH ratio, while a significant decreasing (P<0.05) was in TSH and FSH levels in sterile patient women with hyperthyroidism when compared with control group, and there was a positive significant (P<0.05)correlation between T3,T4 and LH,PRL , testosterone and LH/FSH ratio  , while the relationship was negative significant (P<0.05)between T3,T4 and TSH and FSH in sterile patient women    and the results showed a positive significant(P<0.05) relationship between TSH and FSH, while there was a negative significant(P<0.05) correlation  between TSH and  T3,T4, LH, PRL , testosterone and LH/FSH ratio in sterile women  patients with hyperthyroidism.Key words: Thyroid hormones, Infertility, Hyperthyroidism, TSH, FSH, Prolactin.